Investigation of the sintering and melting of JSC-2A lunar regolith simulant. Issue 9 (15th June 2020) - Zocca, Andrea; Fateri, Miranda; Al-Sabbagh, Dominik; Günster, Jens
Abstract: Future lunar exploration can benefit greatly from In-Situ Resource Utilization. Accordingly, the in-Situ Resource Utilization approach highlights the need for detailed analysis of lunar regolith. In this study, JSC-2A simulant was studied regarding its sintering and melting behaviour using Differential Thermal Analysis under ambient and inert conditions. The minerals at the crystalline peaks were determined using X-Ray Diffraction analysis. Moreover, melting droplet shape and wetting behaviour of pressed regolith samples of different particle size distributions were studied by Hot Stage Microscopy technique. Hot Stage Microscopy experiments were performed at different heating rates under ambient conditions. Bloating effects within the solidified samples were then qualitatively examined by X-ray tomography. Lastly, the optimization of processing strategies for the Additive Manufacturing of lunar regolith is discussed.